Increased iris thickness and association with primary angle closure glaucoma. Issue 1 (7th June 2010) - Wang, B-S; Narayanaswamy, A; Amerasinghe, N; Zheng, C; He, M; Chan, Y-H; Nongpiur, M E; Friedman, D S; Aung, T
Abstract : Aims: To investigate the relationship between quantitative iris parameters and angle closure disease. Methods: Participants with angle closure were recruited prospectively from glaucoma clinics. Anterior segment optical coherence tomography (AS-OCT) was performed under standardised dark conditions. Customised software was used on horizontal AS-OCT scans to measure iris thickness at 750 um (IT750) and 2000 um (IT2000) from the sclera spur, maximal iris thickness (ITM) and cross-sectional area of the iris (I-Area). Results: 167 Angle closure (consisting of 50 primary angle-closure (PAC), 73 primary angle closure glaucoma (PACG) and 44 fellow eyes of acute PAC) and 1153 normal participants were examined. After adjusting for age, sex, pupil size and anterior chamber depth, mean IT750 (0.499 vs 0.451 mm, p<0.001), IT2000 (0.543 vs 0.479 mm, p<0.001), ITM (0.660 vs 0.602 mm, p<0.001) and I-Area (1.645 vs 1.570 mm 2, p=0.014) were significantly greater in angle closure (combined groups) versus normal eyes. Multivariate adjusted odd ratios (OR) of each parameter for the angle closure as compared with normal eyes were: IT750 OR1.7 (95% CI 1.1 to 2.7, p=0.032); IT2000 OR2.2 (95% CI 1.3 to 3.8, p=0.006) and ITM OR2.2 (95% CI 1.3 to 3.6, p=0.003), respectively, per 0.1 unit increase. Conclusions: Increased iris thickness is associated with angle closure.